Architecture tailoring of MoO3 nanostructures for superior ethanol sensing performance. (January 2019) - Mandal, Biswajit; Aaryashree,; Das, Mangal; Than Htay, Myo; Mukherjee, Shaibal
Graphical abstract: Highlights: MoO3 nanobelts and MoO3 nanofibers were hydrothermally synthesized. Architecture tailoring and defect control of MoO3 nanostructures possible through pulsed temperature hydrothermal growth. Transformation of MoO3 nanobelts into surface defective MoO3 nanofibers were systematically investigated. MoO3 nanofibers based sensor showed superior ethanol sensing properties compared to MoO3 nanobelts. Defect control ethanol sensing mechanism of MoO3 nanofibers were explained. Abstract: Alteration of the architecture of molybdenum oxide nanostructure from nanobelts to nanofibers has been achieved by applying frequency-dependent pulsed temperature during hydrothermal growth. The nanostructures was characterized by field emission scanning electron microscopy, X-ray diffraction, high-resolution transmission electron microscopy, selected area electron diffraction pattern and N2 adsorption-desorption analyses. The results revealed that MoO3 nanofibers had better crystalline properties, higher surface area and surface defects as compare to MoO3 nanobelts. The MoO3 nanofibers were used to sense volatile organic compounds (VOCs). VOC sensing studies revealed that sensor using MoO3 nanofibers offered a drastically enhanced response as compared to that with MoO3 nanobelts. The superior sensing performance of the MoO3 nanofiber sensor is attributed to the increase of surface area and surface defect sites in MoO3 nanofibers.